Pemanfaatan Pengolahan Citra untuk Identifikasi Wajah pada Sistem Keamanan Indonesia - Salsabila Putri Hati Siregar; Zulia Lestari Nasution; Aninda Evioni; Khoiratul Azmi (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Image processing is a branch of computer science that is growing rapidly and is widely used in various fields, including in security systems. Face identification is one of the main applications of image processing that aims to recognize and distinguish individual faces in a system. The methods used in face identification involve various techniques, such as facial feature detection, characteristic extraction, and classification using machine learning algorithms. This article discusses the application of image processing in a security system based on face identification and the technology used to improve the accuracy and reliability of the system. The results of the study show that the combination of deep learning algorithms with image pre-processing techniques can increase the success rate of face identification in security systems.